Non-invasive evaluation of therapeutic response in keloid scar using diffuse reflectance spectroscopy - Hsu, Chao-Kai; Tzeng, Shih-Yu; Yang, Chao-Chun; Lee, Julia Yu-Yun; Huang, Lynn Ling-Huei; Chen, Wan-Rung; Hughes, Michael; Chen, Yu-Wen; Liao, Yu-Kai; Tseng, Sheng-Hao (Biomedical optics express, 2015)
The pathogenesis and ideal treatment of keloid are still largely unknown, and it is essential to develop an objective assessment of keloid severity to evaluate the therapeutic response. We previously reported that our diffuse reflectance spectroscopy (DRS) system could assist clinicians in understanding the functional and structural condition of keloid scars. The purpose of this study was to understand clinical applicability of our DRS system on evaluating the scar severity and therapeutic response of keloid. We analyzed 228 spectral data from 71 subjects with keloid scars. The scars were classified into mild (0-3), moderate (4-7) and severe (8-11) according to the Vancouver scar scale. We found that as the severity of the scar increased, collagen concentration and water content increased, and the reduced scattering coefficient at 800 nm and oxygen saturation (SaO2) decreased. Using the DRS system, we found that collagen bundles aligned in a specific direction in keloid scars, but not in normal scars. Water content and SaO2 may be utilized as reliable parameters for evaluating the therapeutic response of keloid. In conclusion, the results obtained here suggest that the DRS has potential as an objective technique with which to evaluate keloid scar severity. In addition, it may be useful as a tool with which to track longitudinal response of scars in response to various therapeutic interventions.